Longitudinal changes in cognition in early Parkinson's disease patients with REM sleep behavior disorder. (June 2016) - Chahine, L.M.; Xie, S.X.; Simuni, T.; Tran, B.; Postuma, R.; Amara, A.; Oertel, W.H.; Iranzo, A.; Scordia, C.; Fullard, M.; Linder, C.; Purri, R.; et al.
Abstract: Introduction: Cognitive decline is common in Parkinson's disease (PD), and identifying patients at highest risk for it is essential. We aimed to examine the effect of possible REM sleep behavior disorder (pRBD) on rate of cognitive decline in early PD, for both global cognition and in specific cognitive domains. Methods: Parkinson's Progression Markers Initiative (PPMI) is a multi-site, international study of PD patients untreated at enrollment. pRBD was assessed with the REM sleep behavior disorder questionnaire (RBDSQ). Global cognition was assessed at baseline and annually using the Montreal Cognitive Assessment (MoCA) and a cognitive battery. Linear mixed effects models were used to examine the relationship between pRBD (RBDSQ ≥ 6) and rate of change in cognitive variables. Age, sex, years of education, and baseline motor and cognitive scores were included as covariates. Results: The baseline sample consisted of 423 individuals with PD, mean age 61.7 years and 65.5% male. Data was available on 389, 366, and 196 participants at 1-year, 2-year, and 3-year follow-up respectively. Possible RBD occurred in 108 (25.5%) at baseline. In multivariate analyses, baseline RBD was associated with greater annual rate of decline in MoCA score (β = −0.34, 95%CI −0.54, −0.13, p < 0.001), Symbol Digit Modalities Test (β = −0.69, 95%CI −1.3, −0.09, p = 0.024), and Hopkins Verbal Learning Test-Revised, delayed free recall (β = −0.21, 95%CI −0.41, −0.013, p = 0.037). Conclusions: Possible RBD is common in early PD and predicts future cognitive decline, particularly in attention and memory domains. Highlights: PD with pRBD have greater rate of decline in global cognition vs. those without. Attention and memory domains are preferentially at risk of decline in PD with pRBD. PD with pRBD have greater odds of mild cognitive impairment vs. those without.